Evaluating effectiveness of Sea Turtle Conservation Program in Vietnam - Tran, Thi Minh Hang; Luu, Thi Tram Anh; Nguyen, Manh Khai (Hue University Journal of Science: Natural Science, 2025)
Vietnam is home to five rare sea turtle species that nest and inhabit its coastal areas (Chelonia mydas, Eretmochelys imbricata, Lepidochelys olivacea, Caretta caretta, and Dermochelys coriacea). However, these species are increasingly threatened by environmental pollution, illegal hunting, and climate change. This study employs a survey-based approach to evaluate the effectiveness of Vietnam’s Sea Turtle Conservation Program. A set of five criteria was proposed and finalised by using a two-round Delphi survey, including (1) management methods, (2) stakeholder participation and contributions, (3) education, communication and community awareness, (4) scientific contributions, and (5) program sustainability. The results indicate that the program is effective, with all evaluation indicators scoring above 76%, especially the program management and stakeholder participation. However, the program still depends heavily on international funding, as domestic and private sector contributions remain limited; consequently, its scientific output is inadequate, relying on outdated and difficult-to-access data. The study proposes several solutions relating to the implementation regime, awareness raising, and sustainable financing to ensure the program’s long-term sustainability and impacts.